Miositis aguda postinfecciosa. - Tori Tori, Carlos (2013)
A seven year old patient in described with acute focal myositis, following an influenza-like infection, involving exclusively the gastroenemius and soleus muscles. The patient improved only with bed rest and symptomatic treatment and made a full recovery in three days. Laboratory studies showed a normal white blood count with an increase in the band forms, elevated SGOT, DHL, and CPK, all of which returned to normal after one week. The patient remains asymptomatic one month after his discharge.